E-project based learning using animation in primary schools - Anuar Mohd Yusof (2010)
This research paper shares a case study of a group of primary school students and their involvement in eProjBL. eProjBL was designed to capitalize both the advantages of Project-based Learning (PBL) and e-learning with a blended learning environment to enhance the learning process of a group of primary school students in a particular topic in science. PBL is the one of conceptual framework of learning model from the constructivist theory and it is "a model for classroom activity that shifts away from the usual classroom practices of short, isolated, teacher-centered lessons". PBL also recognizes the fact that active learners learn better in highly interactive environment. By marrying technology into the PBL, eProjBL was used as a catalyst to motivate the students to become exploreres and researchers. The primary students were given eProjBL content with an animation task needs to be completed by the end of the project. The finished animation projects were evaluated by their teachers using the rubrics metric table of the project. The main purpose of this research study was to investigate the student's perception on the eProjBL content and their engagement in this new blended learning environment utilizing the creation of an animation project. The student's perception on this blended learning environment were found to be positive, starting that they had fun, felt good and gained new knowledge. Majority of the students expressed that they would like to have this type of activity in their future classess as well as in other subjects. The findings of this study also shows that students were engeged in the eProjBL animation activity with development and enhancement of new skill such as creativity, computer literacy, team work collaboration, designing, researching and writing.